2019
DOI: 10.4236/oalib.1105422
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Private Commercial Bank in Corporate Social Responsibility with Reference to Islami Bank Bangladesh Limited

Abstract: This paper aims at exploring how sharia-based financial institution like IBBL performs corporate social responsibilities in Bangladesh in contrast with conventional banking systems. In the era of globalization, to meet the subsequent monetary crisis, IBBL addresses the social and monetary concerns by undertaking programs along with humanitarian & catastrophe relief, education, health, sport, arts & culture to benefit the society. The study reveals a total of 3528 million Taka as CSR expenses by means of examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Several studies (Hadfield-Hill, 2014; Perez and Del Bosque, 2015; Fatma and Rahman, 2016) globally argued that the CSR activities in banks give emphasize the perception of beneficiaries for focusing on the functional values. Some studies (Ullah and Rahman, 2015; Ali and Rahman, 2015; Miah et al , 2019) have identified the impacts of CSR activities of banks based on the information of annual reports. Again, other studies have revealed CSR impacts of Banks based on different perspectives like expenditure for community development and services (Umar and Musa, 2020), the attitude of employees (Rahman et al , 2016) and the perception of employees and clients (Rana, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Several studies (Hadfield-Hill, 2014; Perez and Del Bosque, 2015; Fatma and Rahman, 2016) globally argued that the CSR activities in banks give emphasize the perception of beneficiaries for focusing on the functional values. Some studies (Ullah and Rahman, 2015; Ali and Rahman, 2015; Miah et al , 2019) have identified the impacts of CSR activities of banks based on the information of annual reports. Again, other studies have revealed CSR impacts of Banks based on different perspectives like expenditure for community development and services (Umar and Musa, 2020), the attitude of employees (Rahman et al , 2016) and the perception of employees and clients (Rana, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%